Long‐term preservation of lean mass and sustained loss of fat mass after completion of an intensive lifestyle intervention in older adults with obesity and type 2 diabetes - Robert G Memelink; Aveline Hijlkema; Bas Valentin; Martinet T Streppel; Wilrike J Pasman; Suzan Wopereis; Johan deVogel‐van den Bosch; Michael Tieland; Josje D Schoufour; Ivan Bautmans; Peter JM Weijs (Wiley, 2024)
Abstract Introduction Lifestyle interventions combining caloric restriction with resistance exercise have the potential to preserve lean mass during weight loss. Additional protein intake can further improve lean mass. However, it is unclear whether these effects are sustained after completion of the intervention. This study aimed to evaluate the long‐term effect of a 3‐month lifestyle intervention, with or without supplementation of a protein drink, to preserve lean mass in older adults with obesity and type 2 diabetes at 6 months post‐intervention. Methods Adults (n = 123) aged ≥55 years with obesity and type 2 diabetes were enrolled in a 3‐month intensive lifestyle intervention including a hypocaloric diet, resistance exercise and high‐intensity interval training. Participants were randomized to either receive a leucine and vitamin D‐enriched protein drink or an isocaloric control drink. The 3‐month intervention was followed by a 6‐month phase without intervention. At baseline, 3 and 9 months (follow‐up) body composition, physical functioning, physical activity and quality of life were assessed. Statistical analyses were performed using linear mixed models. Results Body weight loss was largely sustained at follow‐up (−2.1 kg compared to baseline, 95% CI [−2.8, −1.5]) and comprised a sustained loss of fat mass (−2.6 kg, 95% CI [−3.2, −2.0]) with a simultaneous gain of lean mass (+0.7 kg, 95% CI [+0.2, +1.2]). Improvements in 400 m walk speed (+0.05 m/s, 95% CI [+0.03, +0.08]) and chair stand test time (−1.5 s, 95% CI [−1.9, −1.1]) were sustained at follow‐up. There were no differences in these changes between the protein supplementation group and the control group at follow‐up. Conclusions Older adults with obesity and type 2 diabetes preserved their lean mass, their loss of fat mass and their improvements in physical functioning at 6 months post‐intervention. Protein supplementation during intervention did not affect outcomes at follow‐up.